Assessing the Effectiveness of Hormonal Aromatase inhibitors (AI) Therapy in Hormone Receptor Positive Post-Menopausal Breast Cancer Patients: A Systematic Review - Perdiyana , Angki; Lesmana , Agri; Sitompul , Dea Syafira Alamsyah; Wijayanti , Fakhira Ayu; Alrasyid , Miko Dharma; Wiguna , Naufal Yafi Rais; Sutomo , Tharisa Novianti Syabania; Nugraha, Deity; Fitriani, Elies (PT BMW Journal Sejahtera, 2024)
Background: Endocrine therapy is a cornerstone in the treatment of breast cancer for patients who are hormone receptor-positive (HR+). Aromatase Inhibitors are a key option for managing HR+ breast cancer in postmenopausal women. Objective: This study investigates the efficacy of Aromatase Inhibitors in postmenopausal women with HR+ breast cancer, focusing on their therapeutic benefits and associated risks. Methods: A comprehensive literature review was conducted using the Cochrane, Google Scholar, PubMed, Science Direct, ClinicalTrials.gov, and Scopus databases, adhering to PRISMA guidelines. Study quality was evaluated using the Risk of Bias for Randomized Trials (RoB 2.0) tool. Results: Aromatase Inhibitors function by inhibiting the aromatase enzyme, effectively reducing estrogen production. While they can be used with other therapies such as metformin or saracatinib, these combinations are not significantly more effective. Aromatase Inhibitors have been shown to enhance cognitive function and alleviate some depressive symptoms, although they may increase the risk of depression and anxiety in some patients. Conclusion: Aromatase Inhibitors are an effective treatment for HR+ breast cancer in postmenopausal women. However, the potential psychological side effects, such as depression and anxiety, require careful management during therapy.